'Emigrants in the Traditional Sense'? — Irishness in England, Contemporary Migration and Collective Memory of the 1950s. Issue 2 (November 2015) - Scully, Marc
Invocations of the experiences of previous generations of Irish emigrants have been frequent in discussions of the current wave of Irish emigration. This paper considers the mediating effects of viewing contemporary migration through the prism of past migrations. In particular, it is argued that the 'postmemory' of 1950s emigration from Ireland, and the experiences of Irish migrants in English cities, forms a transnational dominant narrative, against which the experiences of contemporary migrants are rhetorically arranged. Drawing on interview and focus group extracts from a study of Irish 'authenticity' in England, the paper demonstrates how subsequent generations of migrants, and those of Irish descent construct a collective memory of the 1950s experience. It also discusses how this narrative appears in Irish governmental discourses as a conveniently usable past, that seeks to emphasise the agency of contemporary migrants, and in so doing alleviate state responsibility for emigration.